Comparison between bidirectional Stratafix® barbed suture and conventional suture in laparoscopic myomectomy: a retrospective study - Kentaro Nakayama; Sultana Razia; Masako Ishikawa; Hitomi Yamashita; Tomoka Ishibashi; Hiroki Sasamori; Kiyoka Sawada; Sonomi Kurose; Seiya Sato; Satoru Kyo (BMC, 2020)
Abstract Background Laparoscopic myomectomy (LM) is one of the techniques feasible for the treatment of intramural myoma. This technique is reported to be difficult when large fibroids are involved because of excessive blood loss during surgery. Skillful and fast suturing appears to be associated with reduced blood loss during LM. In this study we compared the surgical outcomes of using bidirectional Stratafix® barbed suture versus conventional suture during LM. Methods This retrospective study included all patients who underwent LM for the treatment of intramural myoma in our institution between 2015 and 2020. The patients were divided into 2 groups according to the technique of suturing during LM: Group 1 comprised patients in whom Stratafix® barbed suture was used (n = 29), and group 2 comprised those in whom conventional suture was used (n = 15). Data of patient age, myoma size, the number of myoma nodes, hemoglobin levels, total operation time, total suturing time, and blood loss during surgery were compared between the 2 groups. Results No significant differences in age (p = 0.463) or myoma size (P = 0.373) were observed between the 2 groups. Operation time (P = 0.0104), suturing time (P = 0.007), and blood loss (P = 0.0375) during surgery were significantly less with Stratafix® barbed suture than with conventional suture. No patient required intraoperative transfusion or conversion to laparotomy. Conclusion The use of bidirectional barbed suture reduces operation time, suturing time, and blood loss. As these new sutures have barbs, no knot-tying is required; thus, continuous suturing becomes very simple and maintaining hemostasis is easy. Unskilled gynecological surgeons who apply this suture technique can also perform LM easily. As the bidirectional barbed suture has multiple points of fixation, this suture technique can reapproximate tissue securely, which reduces the chances of reoperation because of proper suture knotting. Therefore, bidirectional Stratafix® barbed sutures could be an optimal and efficient alternative to conventional sutures for use by gynecological surgeons in Japan.